Divine Control in Islam: A Pathway to Ethical Workplace Behavior in Modern Organizations - Zakīya, Muḥammad Rāġib (Journal of management, spirituality & religion, 2026)
This study explores divine control in Islam, which includes the dimensions of ikhtiyar (human effort), tawakkul (reliance on Allah), and qadr (divine decree), and its role in shaping Islamic work ethics in modern organizations. The study used a qualitative phenomenological approach. Semi-structured interviews were conducted with Islamic scholars and Islamic psychology experts to gain insight into how these dimensions influence workplace behavior. The results revealed that ikhtiyar fosters responsibility and integrity, tawakkul promotes emotional resilience and collaboration, and qadr instills acceptance and gratitude, creating a balanced approach to ethical work behavior. These dimensions collectively shape an ethical, motivated, and harmonious work environment. Therefore, organizations can integrate divine control in Islam into their management practices to enhance employee ethical behavior. This study contributes to the growing literature on Islamic management by presenting divine control in Islam as a comprehensive framework for understanding and underpinning Islamic work ethics in organizational settings.